Assessing the Strength Characteristics of Cement Mortar using Eggshell Powder and Kenaf Fiber - Damahuri, Danny Iskandar; Hilmi Kosnin; Abd Sukor Sarif (Progress in Engineering Application and Technology, 2024)
In the relentless pursuit of sustainable and eco-friendly construction materials, this research delves into the potential of eggshell powder and kenaf fiber to enhance the strength characteristics of cement mortar. Driven by the abundance of eggshells as waste and the promising mechanical properties of kenaf fibers, this study explores their synergistic effects on the strength and performance of this fundamental construction material. Through rigorous experimentation, the research meticulously examines the impact of varying eggshell powder and kenaf fiber content on the compressive, tensile, and flexural strengths of cement mortar. Advanced scanning electron microscopy (SEM) analysis unravels the intricate microstructure of the composite material, elucidating the interfacial interactions between the eggshell powder, kenaf fibers, and cement matrix. Beyond mere strength enhancement, the investigation delves into the potential durability and environmental benefits of utilizing these sustainable substitutes. By assessing the water absorption, porosity, and freeze-thaw resistance of the eggshell-kenaf reinforced mortar, the study seeks to ensure its long-term viability and resilience in real-world construction applications. Ultimately, this research aims to bridge the gap between sustainability and performance in the construction industry. By comprehensively assessing the strength, durability, and environmental footprint of incorporating eggshell powder and kenaf fiber into cement mortar, the study paves the way for a more sustainable and resource-efficient future for construction.